How will a robot change your life?. - Keramas, J.G (IEEE Robotics and automation magazine)
Any way you look at it, the robot has an exciting future. Soon, we can expect the robot to move out of the factory and enter the domestic and business worlds. The domestic robot will appear in the home as an electronic pet and soon will develop the ability to perform useful tasks there. The sensory ability of all robots will greatly improve. In the long run, robots will acquire the capabilities they have been described as having in the movies and science fiction books. Self-reproducing factories may be placed on the moon or on other planets to help meet our growing needs for energy and goods. Inspirational changes are on the way as robots become the helpers that humans have always dreamed of